2003
DOI: 10.1016/s0956-5663(02)00157-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical whole-cell biosensor using Chlorella vulgaris designed for monitoring herbicides

Abstract: . Optical whole-cell biosensor using Chlorella vulgaris designed for monitoring herbicides. Biosensors and Bioelectronics, Elsevier, 2003, 18 (4), pp.547-463. <10.1016/S0956-5663(02)00157-4>. & Bioelectronics, 2003& Bioelectronics, , 18(4), 457-63, doi:10.1016 Biosensors AbstractAn optical biosensor was designed for determination of herbicides as aquatic contaminants. Detection was obtained with immobilised Chlorella vulgaris microalgae entrapped on a quartz microfibre filter and placed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(75 citation statements)
references
References 26 publications
3
69
0
3
Order By: Relevance
“…Although the cell showed good sensitivity and reproducibility in the tests with a few types of heavy metals, further work is required to incorporate the cell into a biosensor. The factors which influence the response of cell, such as the condition of the culture, the number of cell to be used in detection, the detection condition such as pH are yet to be studied [2], [3], [32]. The cells cultured respond differently in different growth stage, while different number of cells used affects the signal produced as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cell showed good sensitivity and reproducibility in the tests with a few types of heavy metals, further work is required to incorporate the cell into a biosensor. The factors which influence the response of cell, such as the condition of the culture, the number of cell to be used in detection, the detection condition such as pH are yet to be studied [2], [3], [32]. The cells cultured respond differently in different growth stage, while different number of cells used affects the signal produced as well.…”
Section: Resultsmentioning
confidence: 99%
“…pH is most widely studied factor, as bioconponents are affected by the pH of the environment [32], [36].…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Pazmiño et al [14] have suggested that synthesis of auxin could be disrupted due to higher concentration of 2,4-D, whereas carbon assimilation and photochemical reaction might be strengthened through low concentration of 2,4-D. Previous research done by Védrine et al [15] on wholecell biosensor using C. vulgaris for monitoring herbicides showed that the algae could response affectively in the presence of atrazine. In this study, an optimal pH of 7 was maintained in room temperature.…”
Section: B the Exposure Of Cells To Pesticidesmentioning
confidence: 99%
“…For example, an optical fiber based biosensor was developed for atrazine and endrine monitoring in water using Scenedesmus subspicatus cells, immobilized on filter paper and covered with a thin alginate layer hardened with calcium chloride (Frense et al, 1998). Chlorella vulgaris was immobilized at the tip of an optical fiber bundle placed inside a homemade microcell (Naessens et al, 2000), or in a rotating support holding up to five different membranes to increase the number of assays (Védrine et al, 2003), and used for the detection of herbicides affecting photosystem II (PSII) such as triazines (atrazine, simazine) or phenylureas (diuron, isoproturon) herbicides at sub-µgL -1 concentration level. NguyenNgoc et al (2007) investigated the response of a microalgal biosensor to the herbicide Diuron® by measuring the variation of the chlorophyll fluorescence of Chlorella vulgaris strain conveniently entrapped into a sol-gel translucent support.…”
Section: Microalgal Whole Cell Biosensorsmentioning
confidence: 99%